The impact of business group diversification on emerging market multinationals: evidence from Latin America - Borda-Reyes, Armando (2012)
This article explored whether the benefits of business group diversification on the scope-performance relationship varies depending on the level of development of the network of subsidiaries and the region of operation of the focal firm. To test the hypothesis presented, a panel data with fix effects models was used on a sample of Latin American firms. The results suggested that business group diversification has the capacity to generate value in the internationalization process of their affiliates. However, the benefits of business group diversification are location bound within the region (Americas) but they are not related to the level of development of the targeted countries.